Long noncoding RNA TM1P3 is involved in osteoarthritis by mediating chondrocyte extracellular matrix degradation. Issue 8 (19th March 2019) - Li, Yufei; Li, Zuowei; Li, Chunyun; Zeng, Yuelin; Liu, Yong
Abstract: Background and Objectives: Osteoarthritis (OA) is a widespread degenerative joint disease characterized by articular cartilage degradation and is the leading cause of physical disability. Noncoding RNAs, especially long noncoding RNAs (lncRNAs) and microRNAs, are involved in the degradation of the chondrocyte extracellular matrix (ECM) in patients with OA. The present study was aimed to investigate the effects of lncRNA and miR‐22 on the degradation of the chondrocyte ECM and underlying mechanisms. Methods: To simulate conditions found in OA, primary cultured chondrocytes were treated with IL‐1, TGF‐β, or sb525334. Real‐time PCR and Western blot analysis were performed to detect expressions of miR‐22, lncRNA‐TM1P3, ALK1, MMP13, pSMAD1/5, SMAD1, and pSMAD5. Small interfering RNAs and a miR‐22 mimic or inhibitor were utilized to determine lncRNA‐TM1P3 knockdown and miR‐22 overexpression or inhibition. Results: The lncRNA‐TM1P3 significantly upregulated in patients with OA, accompanied by the downregulation of miR‐22 and upregulation of pSMAD1/5 and MMP13, which ultimately resulted in the degradation of the chondrocyte ECM in patients with OA. Bioinformatics analysis predicted miR‐22 as a target of both lncRNA‐TM1P3 and MMP13. The lncRNA‐TM1P3 knockdown significantly increased the expression of ALK1, a corresponding increase in ECM degradation was observed by affecting the phosphorylation of SMAD1/5 and the expression of MMP13, which did not affect the expression of ALK1. Conclusions: These findings demonstrated that the lncRNA‐TM1P3/miR‐22/TGF‐β signaling/MMP13 axis is involved in the degradation of chondrocyte ECM in patients with OA, which could provide novel therapies for OA treatment.